ANALISIS FAKTOR YANG MEMENGARUHI PERILAKU MASYARAKAT TERHADAP UPAYA PENCEGAHAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS MUTIARA, ASAHAN - Eka Sri Handayani (Jurnal Kajian Kesehatan Masyarakat, 2020)
The general objective of this research is to identify the factors that influence the behavior of the community in prevention efforts dengue fever Dengue in the region Seek the Pearl Regency Range town of Kisaran Sub of the year 2018. This research population is dengue dengue fever patients in the Asahan Regency Mutiraa health centers totaled 40 people.The sample of this research is all the patient sufferer DBD treatment and coming Health Clinics saw a Pearl in June to December 2017, as many as 40 people, with a total of sampling that is the total population of 40 people become As for the results of the study sample was Contained prevention efforts based on the respondent's Knowledge then the DBD respondents have a good Community Behaviour in dengue fever prevention efforts in the area of Asahan Regency. Pearls of clinics of 153.20% There are DBD prevention efforts, based on the attitude of the respondent the respondent then has a good Community Behaviour in dengue fever prevention efforts in the area of Asahan Regency. Pearls of clinics of 913.30%., there are DBD prevention efforts based on family support then the respondents have a good Community Behaviour in dengue fever prevention efforts in the area of Asahan Regency. Pearls of clinics of 420.80%, there is DBD prevention efforts based on the health facilities then the respondent has a good chance of Community Behaviour in dengue fever prevention efforts in the area of Asahan Regency. Pearls of clinics of 365.70% and there is DBD prevention efforts based on Education then the respondent has a good chance of Community Behaviour in dengue fever prevention efforts in the area of Asahan Regency Pearls Clinics 242.00%, there are prevention efforts based on the work of the DBD then respondents had Community Behavior good in Dengue prevention efforts in the area of public health District of Asahan. Pearl 156.00%.